2009
DOI: 10.1111/j.1742-4658.2009.07195.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant oxylipins: Plant responses to 12‐oxo‐phytodienoic acid are governed by its specific structural and functional properties

Abstract: One of the most challenging questions in modern plant science is how plants regulate their morphological and developmental adaptation in response to changes in their biotic and abiotic environment. A comprehensive elucidation of the underlying mechanisms will help shed light on the extremely efficient strategies of plants in terms of survival and propagation. In recent years, a number of environmental stress conditions have been described as being mediated by signaling molecules of the oxylipin family. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
85
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 109 publications
0
85
0
Order By: Relevance
“…The mediator of such OPDA retrograde signaling, however, seems to be not the cysteine per se but a change in redox potential caused by increased concentration of thiol groups. Increased cysteine synthesis leads to synthesis of glutathione that can convey the redox signal to the TGA transcription factors, which have been shown previously to be redox-sensitive (19). Thus, sulfur metabolites are necessary for the OPDA-triggered retrograde signaling.…”
mentioning
confidence: 99%
“…The mediator of such OPDA retrograde signaling, however, seems to be not the cysteine per se but a change in redox potential caused by increased concentration of thiol groups. Increased cysteine synthesis leads to synthesis of glutathione that can convey the redox signal to the TGA transcription factors, which have been shown previously to be redox-sensitive (19). Thus, sulfur metabolites are necessary for the OPDA-triggered retrograde signaling.…”
mentioning
confidence: 99%
“…Genetic evidence in maize (Zea mays) supports a role for JA biosynthesis in the survival of biotic stress, regulation of senescence, and cell death processes mediating male sex determination (8,9). As a precursor, 12-OPDA can trigger developmental processes and defense signaling different from JA-Ile (10)(11)(12). During physiological stress, 12-OPDA binds cyclophilin 20-3 which facilitates recruitment of a cysteine synthase complex…”
mentioning
confidence: 99%
“…1) A transcriptome analysis in Arabidopsis showed that many genes were induced by OPDA, but not by JA.…”
mentioning
confidence: 99%